Digitalization and Digital Competence in Educational Contexts A Nordic Perspective from Policy to Practice - Willermark, Sara; Olofsson, Anders D.; Lindberg, J Ola (Taylor & Francis, 2024)
Digital competence, teachers, infrastructures for teaching and working, challenges